EVALUASI PROSES PEMBUATAN LAPORAN INTERNAL DAN PEMANFAATAN INFORMASI REKAM MEDIS RUMAH SAKIT ISLAM IBNU SINA PEKANBARU 2015 - Octaria, Haryani; Jepisah, Doni (PROGRAM STUDI DIII KEPERAWATAN UNIVERSITAS ABDURRAB PEKANBARU, 2016)
Reporting hospital is an organization tool that aims to be able to generate reports in a quick, precise and accurate. This type of reporting consists of internal and external reports. From the observations which the author did to the internal hospital report Islam Ibnu Sina Pekanbaru, still found error calculation by nurses in Inpatient census room and Out patient so the summation becomes out of sync. With the rekapan of an error report is not accurate and the information needed to be less precise. Internal reporting utilized by the hospital especially the Director as well as the Foundation. As for the research purposes for causing Internal Report making process and utilization of medical record Information in hospital Islam Ibnu Sina Pekanbaru 2015.The design of this research is descriptive research with qualitative approach. Descriptive research is a method of research conducted with the goal to create a picture or descriptive of a situation objectively conducted in April-May 2016 with 3 Informant, Deputy Director, head of Unit, medical record and medical record Clerk.The research of data processing for medical record in hospital Islam Ibnu Sina be it Assembling, Coding, Indexing, and reporting already done with optimal. The process of making the report and the information already put to good use by the Director or such a Foundation report MOR. And for the utilization of medical record information used for decision making research and education.The conclusion to the Medical Record data processing already carried out with optimal. The process of creating reports and information were already well underway, and the utilization of medical record information already utilized by the Board of Directors for decision making. His medical record officers must quickly in input and merekap every day, room nurses should carefully in making the census, and the hospital must be responsible for protecting information.